Synthesis of Vaccinia Viral Proteins in Cytoplasmic Extracts: I. Incorporation of Radioactively Labeled Amino Acids into Polypeptides - Katz, Ehud (1969)
Polypeptide synthesis has been studied in cell-free systems prepared from vaccinia virus-infected and uninfected HeLa cells. Cytoplasmic extracts containing endogenous messenger ribonucleic acid were used. Amino acid incorporation into hot trichloroacetic acid-precipitable material was linear for 15 to 20 min at 37 C. The initial rate of protein synthesis was approximately 15% of the rate in intact cells. Optimal conditions for polypeptide synthesis were similar in cell-free systems prepared from infected or uninfected cells. Requirements for an energy source and Mg(++) were demonstrated. The optimal Mg(++) concentration was 4 to 5 mm. Ribonuclease, puromycin, and cycloheximide were inhibitory. The molecular weights of the polypeptides labeled in the cell-free systems, as determined by gel filtration in 5 m guanidine hydrochloride, ranged from 16,000 to above 68,000. Polyacrylamide gel electrophoresis indicated that the polypeptides labeled in cell-free extracts of uninfected and infected cells were different. The latter closely corresponded in electrophoretic mobility with the viral polypeptides made in intact, infected cells.